RETRACTED: PENGARUH PERCEIVED USEFULNESS TERHADAP PURCHASE INTENTION PADA SHOPEE DENGAN CUSTOMER ATTITUDE SEBAGAI VARIABEL MEDIASI - Hidayat, Danny (Universitas Islam Bandung, 2023)
This study aims to analyze the effect of perceived usefulness on purchase intention at shopee with customer attitude as a mediating variable. The type of research used in this research is explanatory research, with the research method being an explanatory survey that emphasizes quantitative methods. The sample is 170 consumers who shop online at Shopee in the city of Padang. The sampling technique was purposive sampling. The data analysis method uses Structural Equation Modeling - Partial Least Square (SEM-PLS). The results of the study show that Perceived usefulness has no significant effect on purchase intention. Perceived usefulness has a significant effect on customer attitude. Customer attitude has a significant effect on purchase intention. Perceived usefulness has a significant effect on purchase intention which is mediated by customer attitude. This research has implications for the online shop Shopee, namely that Shopee is expected to pay more attention to perceived usefulness because it affects customer attitude and purchase intention of consumers who shop online at Shopee. Researchers hope that this research can be developed so that the purchase intention of consumers who shop online at Shopee is increasing by increasing consumer convenience in shopping online using the Shopee application itself so that it can still be accepted as a technological innovation in shopping that helps make it easier for customers to shop for the desired product without have to come to the store in person.